2014
DOI: 10.1158/1535-7163.mct-13-0846
|View full text |Cite
|
Sign up to set email alerts
|

Aurora Kinase Inhibition Induces PUMA via NF-κB to Kill Colon Cancer Cells

Abstract: Aurora kinases play a key role in mitosis and are frequently overexpressed in a variety of tumor cells. Inhibition of aurora kinases results in mitotic arrest and death of cancer cells, and has been explored as an anticancer strategy. However, how aurora inhibition kills cancer cells is poorly understood. In this study, we found that inhibition of aurora kinases by siRNA or small-molecule inhibitors led to induction of PUMA, a BH3-only Bcl-2 family protein, in colorectal cancer cells irrespective of p53 status… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(39 citation statements)
references
References 38 publications
0
39
0
Order By: Relevance
“…Previous studies have shown that NF‐κB pathway and p73 were involved in PUMA activation . However, the phosphorylation level of p65 and the expression of p73 remained unchanged after VB1 treatment.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…Previous studies have shown that NF‐κB pathway and p73 were involved in PUMA activation . However, the phosphorylation level of p65 and the expression of p73 remained unchanged after VB1 treatment.…”
Section: Discussionmentioning
confidence: 85%
“…It can be transcriptionally activated by p53 in response to DNA‐damaging agents . The activation of PUMA by nongenotoxic stimuli is p53‐independent and mediated by different transcription factors, including p53 homologue p73, forkhead box O3a (FoxO3a), and nuclear factor‐kappa B (NF‐κB) . Upon induction, PUMA facilitates mitochondrial outer membrane permeabilization and caspase activation cascade to regulate Bcl‐2‐associated X protein (Bax) activity .…”
Section: Introductionmentioning
confidence: 99%
“…Wang et al has recently reported that PUMA is a direct target of NF-κB and mediates TNF-α-induced apoptosis in vitro and in vivo [24]. Sun et al has also reported that PUMA was directly activated by p65 through the canonical NF-κB pathway, mediating the apoptotic response to mitotic arrest imposed by aurora kinase inhibition [25]. Dynamic changes in lncRNA expression have been demonstrated upon activation of NF-kB signalling.…”
Section: Discussionmentioning
confidence: 99%
“…Our laboratory discovered that inhibition of Aurora‐A increases the Bax/Bcl‐2 expression ratio, a favorable pro‐apoptotic predictor for drug response in AML . The expression of PUMA, another modulator of apoptosis, is significantly increased after suppression of Aurora‐A by siRNA or small‐molecule inhibitors . Inhibition of Aurora‐A also induces expression of the pro‐apoptotic protein Bim and triggers apoptosis in AML cells.…”
Section: Functions Of Aurora‐amentioning
confidence: 99%
“…62 The expression of PUMA, another modulator of apoptosis, is significantly increased after suppression of Aurora-A by siRNA or small-molecule inhibitors. 63 Inhibition of Aurora-A also induces expression of the pro-apoptotic protein Bim and triggers apoptosis in AML cells. Accordingly, pro-apoptotic signals are downregulated by Aurora-A through the phosphorylation and degradation of BimEL, the major splice variant of Bim.…”
Section: Anti-apoptosismentioning
confidence: 99%